2013
DOI: 10.1021/jp4048709
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Acid Adsorption in MFI-Type Zeolites Enabled by the pH-Dependent Ability to Displace Water

Abstract: Downstream processing of biochemical products strongly depends on the interaction between biomolecules and material surfaces that can be influenced greatly by the pH level. In this study, the influence of the pH value on the adsorption of the amino acids glycine, alanine, and lysine in MFI-type zeolite was investigated using density functional theory (DFT) and microcalorimetric experiments. Different pH values were modeled by varying the amino acids protonation states. The investigated protonation states exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 86 publications
3
18
1
Order By: Relevance
“…A large proportion of this observed variation may be due to the different levels of impurities present in available commercial clays employed in most studies (e.g., Table 1). Based on the lower ichthyotoxin removal at pH 9 by all clay minerals tested here (except B4-6), it appears likely that pH-dependent changes in the protonation status of toxin molecules and/or the pH-dependent surface charge of clay minerals is driving their adsorption kinetics [25][26][27]33]. Unfortunately, due to the poorly understood chemical nature of P. parvum ichthyotoxins, the contribution of the ionization state of toxin molecules cannot yet be fully resolved.…”
Section: Clay Screeningmentioning
confidence: 91%
“…A large proportion of this observed variation may be due to the different levels of impurities present in available commercial clays employed in most studies (e.g., Table 1). Based on the lower ichthyotoxin removal at pH 9 by all clay minerals tested here (except B4-6), it appears likely that pH-dependent changes in the protonation status of toxin molecules and/or the pH-dependent surface charge of clay minerals is driving their adsorption kinetics [25][26][27]33]. Unfortunately, due to the poorly understood chemical nature of P. parvum ichthyotoxins, the contribution of the ionization state of toxin molecules cannot yet be fully resolved.…”
Section: Clay Screeningmentioning
confidence: 91%
“…Indeed, the adsorption of a single amino acid into micro-pores of zeolites has been already reported both theoretically [30] and experimentally [31][32][33]. For example, Stückenschneider et al reported the adsorption behavior of lysine on ZSM-5 which has three-dimensional pores with aperture of 5.4 Â 5.6 Å [31]. Krohn and Tsapatsis demonstrated that zeolite BEA can adsorb lysine and arginine [32] and FAU can adsorb arginine [33].…”
Section: Contribution Of the Basic Amino Acid Residues To The Adsorptmentioning
confidence: 98%
“…However, amino acid side chains exposed on the surface of a protein molecule can enter, at least partly, into pores of the zeolites. Indeed, the adsorption of a single amino acid into micro-pores of zeolites has been already reported both theoretically [30] and experimentally [31][32][33]. For example, Stückenschneider et al reported the adsorption behavior of lysine on ZSM-5 which has three-dimensional pores with aperture of 5.4 Â 5.6 Å [31].…”
Section: Contribution Of the Basic Amino Acid Residues To The Adsorptmentioning
confidence: 99%
“…As aforementioned, minerals play a central role during birth of life, and their interactions with amino acids have recently emerged to be a research hotspot . The periodic density functional theory (p‐DFT) calculations of Pantaleone et al showed that the strongest interaction of anatase (101) surface with amino acids corresponds to the dative bonding between the N or O atoms of amino acids and surface‐Ti atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11]13,14] As aforementioned, minerals play a central role during birth of life, and their interactions with amino acids have recently emerged to be a research hotspot. [17][18][19][20][21][22][23][24][25][26][27][28][29] The periodic density functional theory (p-DFT) calculations of Pantaleone et al [24] showed that the strongest interaction of anatase (101) surface with amino acids corresponds to the dative bonding between the N or O atoms of amino acids and surface-Ti atoms. As indicated by the p-DFT results of Rimola et al, [19] glycine adsorption over the silica surface with isolated hydroxyl groups is dominated by canonical isomers.…”
Section: Introductionmentioning
confidence: 99%